Curating immateriality : the work of the curator in the age of network systems - Krysa, Joasia (Brooklyn, NY. : Autonomedia ; [London : Compass Academic, distributor], 2006)
- Curating immateriality : the work of the curator in the age of network systems / Joasia Krysa##- Of sense and sensibility : immaterial labour in open systems / Tiziana Terranova##- Twilight on the widgets : notes on immateriality and value / Marina Vishmidt##- Extract from kurator source code : LXR library functions / Grzesiek Sedek##- Software actions / Geoff Cox##- Flexible contexts, democratic filtering and computer-aided curating : models for online curatorial practice / Christiane Paul##- 'C@C - computer-aided curating' (1993-1995) revisited / Eva Grubinger##- Conceptual transformations of art : from dematerialisation of the object to immateriality in networks / Jacob Lillemose##- Unassignable leakage : a crisis of measure and judgement in immaterial (art) production / Josephine Berry Slater##- Biennale.py 0100101110101101.org & [epidemiC]##- On misanthropy / Alexander R. Galloway & Eugene Thacker##- Annotations on 'I love you' by digitalcraft.org / Franziska Nori##- Net art locator##- The participatory challenge / Trebor Scholz##- Edits from a crumb discussion list theme / Beryl Graham##- An inventory of media art festivals / Piotr Krajewski##- From art on networks to art on platforms (case studies : runme.org, micromusic.net and udaff.com) / Olga Goriunova & Alexei Shulgin##- Cultural labour and immaterial machines / Matteo Pasquinelli.
CCS Gent
Includes bibliographical references.
boek